Usefulness of a newly designed plastic stent for endoscopic re-intervention in patients with malignant hilar biliary obstruction - Tomoda, Takeshi; Kato, Hironari; Kawamoto, Hirofumi; Muro, Shinichiro; Akimoto, Yutaka; Uchida, Daisuke; Matsumoto, Kazuyuki; Horiguchi, Shigeru; Tsutsumi, Koichiro; Okada, Hiroyuki (Endoscopy, 2017)
Background and study aims We designed a new 7-Fr plastic stent for treating self-expandable metal stent (SEMS) obstruction in patients with malignant hilar biliary obstruction (MHBO) via endoscopic re-intervention with the stent-in-stent (SIS) method and evaluated its efficacy.Patients and methods A total of 33 consecutive patients who underwent endoscopic re-intervention for metal stent obstruction after multi-branched SEMS placement were enrolled. The initial SEMSs were placed in two or three biliary branches in 14 and 19 patients, respectively. We retrospectively evaluated the technical and clinical success, and adverse events. Technical success was defined as successful plastic stent placement into all target branches through the lumen of the SEMS.Results The technical success rates were 85.7 % (12/14) and 78.9 % (15/19) in patients who underwent two- or three-branched biliary drainage, respectively. The clinical success rate was 100 % in the 27 patients in whom technical success was achieved. We achieved successful plastic stent placement in more than two branches, using the new plastic stent combined with a conventional plastic stent, in 97.0 % (32/33).Conclusions This new plastic stent was technically feasible for treating stent obstruction via re-intervention with SIS methods.